You are on page 1of 3

# Tarea 5 Ejercicio 38

Multiplicación de monomios

Multiplicar:

1 (a )(− 3a )(a 2 )
2 (3x )(− x y )(− a x )
2 3 2

3 (− m n)(− 3m )(− 5mn )
2 2 3

4 (4a )(− 5a x )(− ay )
2 3 2 2

5 (− a )(− 2ab)(− 3a b )
m 2 x

 1 3  2 2  3 4 
6  x  − a x  − a m 
 2  3  5 

7
 2 m  3 2 4 
 a  a b  − 3a b
4 x
( )
 3  4 

8
 3 3
(
2  1 x a
 − m  − 5a m  − a m  )
 5   10 

9 (2a )(− a 2 )(− 3a 3 )(4a )
10 (− 3b )(− 4a b)(ab)(− 5a x )
2 3 2

11 (a b )(− a )(− 2ab)(− 3a x )
m x 2 2

 1 2  3 2  10 3  3 2 
12  − x y  − xy  − x  − x y 
 2  5  3  4 
RESPUESTAS:

1 (a )(− 3a )(a 2 )

(a )(− 3a )(a 2 ) = 1 ⋅ −3 ⋅1 ⋅ a1+ 2 +1 = −3a 4

2 (3x )(− x y )(− a x )
2 3 2

(3x )(− x y )(− a x ) = 3 ⋅ −1 ⋅ −1 ⋅ a
2 3 2 2
⋅ x 2 + 3+1 ⋅ y = 3a 2 x 6 y

3 (− m n)(− 3m )(− 5mn )
2 2 3

(− m n)(− 3m )(− 5mn ) = −1 ⋅ −3 ⋅ −5 ⋅ m
2 2 3 2 + 2 +1 1+ 3
n = 15m5n 4

4 (4a )(− 5a x )(− ay )
2 3 2 2

(4a )(− 5a x )(− ay ) = 4 ⋅ −5 ⋅ −1 ⋅ a
2 3 2 2 2 + 3 +1 2
x y 2 = 20a 6 x 2 y 2

5 (− a )(− 2ab)(− 3a b )
m 2 x

(− a )(− 2ab)(− 3a b ) = −1 ⋅ −2 ⋅ −3 ⋅ a
m 2 x m +1+ 2 1+ x
b = −6a m + 3b x +1

 1 3  2 2  3 4 
6  x  − a x  − a m 
 2  3  5 

 1 3  2 2  3 4  1⋅ −2 ⋅ −3 2+4 3+1 6 6 4 1
 x  − a x  − a m  = ⋅a x m = a x m = a 6 x 4m
 2  3  5  2⋅ 3⋅5 30 5

7
 2 m  3 2 4 
 a  a b  − 3a b
4 x
( )
 3  4 

2 ⋅ 3 ⋅ −3 m + 2 + 4 4 + x
 2 m  3 2 4 
 a  a b  − 3a b =
4 x
(
3⋅ 4
a ) 18 3
b = − a m + 6b x + 4 = − a m + 6b x + 4
 3  4  12 2

8
 3 3
(
2  1 x a
 − m  − 5a m  − a m  )
 5   10 
 1 x a  − 3 ⋅ −5 ⋅ −1 2+ x 3+1+a
 3 3
( )
 − m  − 5a m  − a m  =
2

5 ⋅10
a m
15 3
= − a x + 2 m a+ 4 = − a x + 2 m a + 4
 5   10  50 10

9 (2a )(− a 2 )(− 3a 3 )(4a )

(2a )(− a 2 )(− 3a3 )(4a ) = 2 ⋅ −1 ⋅ −3 ⋅ 4 ⋅ a1+ 2 + 3+1 = 24a7

10 (− 3b )(− 4a b)(ab)(− 5a x )
2 3 2

(− 3b )(− 4a b )(ab )(− 5a x ) = −3 ⋅ −4 ⋅ 1 ⋅ −5 ⋅ a
2 3 2 3 +1+ 2 2 +1+1
b x = −60a 6b 4 x

11 (a b )(− a )(− 2ab)(− 3a x )
m x 2 2

(a b )(− a )(− 2ab)(− 3a x ) = 1 ⋅ −1 ⋅ −2 ⋅ −3 ⋅ a
m x 2 2 m + 2 +1+ 2 x +1
b x = −6a m + 5b x +1x

 1 2  3 2  10 3  3 2 
12  − x y  − xy  − x  − x y 
 2  5  3  4 

 1 2  3 2  10 3  3 2  − 1 ⋅ −3 ⋅ −10 ⋅ −3 2+1+ 3+ 2 1+ 2 +1 90 8 4 3 8 4
 − x y  − xy  − x  − x y  = x y = x y = x y
 2  5  3  4  2⋅5⋅3⋅ 4 120 4